Rethinking strategic corporate philanthropy: the donation chain approach - Fabiani, Paula Maria de Jancso (2024)
In response to escalating societal requisitions, it becomes imperative for corporations to adopt a more strategic approach to philanthropic donations. This research aims to investigate how the corporate philanthropy process becomes more strategic by engaging multiple stakeholders to create societal value. It introduces the original concept of a Corporate Donation Chain (CDC), which refers to the processes by which a company supplies financial resources to non-profit organizations that implement initiatives with positive societal impacts. The CDC is examined through the lens of supply chain management, utilizing Stakeholder Theory (ST) and the Relational View (RV) as theoretical foundations. This study investigates a revelatory single case study of a Brazilian company, offering empirical evidence to support the formulation of a CDC model and an enhanced Strategic Corporate Philanthropy (SCP) framework. To enhance value creation for society and the company, firms must deepen their understanding and practices on improving stakeholders' engagement and their relations. This research contributes to the theoretical and practical discourse on CP as a strategic aspect of corporate operations. It presents a novel approach by analyzing the CP process from a supply chain perspective, applying ST and RV to examine the CDC, and concentrating on the Brazilian context, a nation facing substantial societal and environmental challenges. Furthermore, it outlines promising directions for future research that can enrich the academic debate surrounding SCP.